Exploring student perceptions of belonging and school climate in two culturally diverse Finnish secondary schools - Alisaari, Jenni; O’Neill, Keith; Kuusela, Anna; Seger, Aleksi; Kimanen, Anuleena; Hammer, Svenja; Viesca, Kara; Khalili, Samaneh (Turun korkeakoulujen yhteiskunnallistaloudellinen tutkimusyhdistys ry., 2026)
Perceptions of belonging and school climate among minoritized students in Finland remain underdeveloped
areas of enquiry in social and educational science. Using a data-driven approach, this explorative study
investigates how minoritized students in lower secondary schools in Finland perceive belonging and
school climate. The data used consisted of 11 group interviews with 55 students (14–16 years old) from
two culturally diverse secondary schools in Finland. The study found that the overall school climate was
perceived to be broadly positive but simultaneously “chaotic”, and inclusion, exclusion, and discrimination
were found to play significant roles regarding students’ sense of belonging. The students interviewed
perceived ethnic diversity as generally accepted and a marker of inclusion; however, non-binary gender
identity was perceived to be a reason for exclusion. The students expressed various experiences with
bullying and discrimination and some students felt that they had to adapt to the school climate to belong.
The study’s diverse school settings offer valuable insights into inclusionary and exclusionary practices,
especially through students’ perceptions of belonging and school climate. To foster a positive climate for
diversity, greater attention must be given to the experiences of minoritized students.